1999
DOI: 10.1016/s0035-9203(99)90368-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive sequelae of severe malaria with impaired consciousness

Abstract: Although cerebral malaria is the most common acute encephalopathy arising in children in Africa little is known of its effect upon the longer-term cognitive development of survivors. In Kenya, we compared the performance of 87 survivors of severe malaria with impaired consciousness to matched community controls on a wide range of tasks, not less than 42 months post illness episode. The presence of cognitive impairment was then related to both the pattern of symptoms at the time of the acute illness and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
160
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(167 citation statements)
references
References 21 publications
7
160
0
Order By: Relevance
“…35 Our own investigations have found that not all children who had seizures go on to develop either neurological or cognitive impairments, although all children who had cognitive impairments had also had at least one seizure. 17 Only a small number of our study children (n ϭ 5) were recorded as having had status epilepticus, and not all of these developed sequelae, either cognitive or neurological. Interestingly, neither of the children whose cognitive development was most globally impaired had incurred Ͼ 3 seizures during the course of their illness, nor had they been in status epilepticus.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…35 Our own investigations have found that not all children who had seizures go on to develop either neurological or cognitive impairments, although all children who had cognitive impairments had also had at least one seizure. 17 Only a small number of our study children (n ϭ 5) were recorded as having had status epilepticus, and not all of these developed sequelae, either cognitive or neurological. Interestingly, neither of the children whose cognitive development was most globally impaired had incurred Ͼ 3 seizures during the course of their illness, nor had they been in status epilepticus.…”
Section: Introductionmentioning
confidence: 87%
“…There have been 2 published studies that have looked at the cognitive and neuropsychological sequelae of cerebral malaria in children, one in The Gambia and the other in Kenya. 16,17 The Gambia study included 36 children who were assessed only in terms of nonverbal functioning and motor development by use of translations of tests standardized for Western populations. The study excluded children who had a Blantyre Coma Score of Ͼ 2 or who had gross neurological sequelae on discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated that children with a history of recurring seizures during acute illness are at risk for cognitive and language impairment [51,[105][106][107][108]. Attention, memory, learning and language impairment from CM can place children at a significant disadvantage in such functional domains as academic achievement and day-to-day adaptive behaviors related to executive function at home or in the community [109][110][111][112].…”
Section: Neuropsychological Sequelae Of CMmentioning
confidence: 99%
“…Children who develop spastic quadriparesis or vegetative state usually die. Residual neurologic sequelae occur in ~10% of immunocompetent people and may include epilepsy and cognitive, behavioral, and language deficits, as well as hemiparesis, blindness, and ataxia [58,60]. The effect of immunosuppression on the incidence of long-term neurologic sequelae is not known.…”
mentioning
confidence: 99%